DESIGNING ISO-BASED FAILURE MANAGEMENT FRAMEWORK TO ENHANCE COMPLAINT MANAGEMENT - Wahyudi, Rahman Dwi; Hadiyat, Mochammad Arbi (JEMIS (Journal of Engineering & Management in Industrial System), 2026)
Complaints are a critical indicator that can reveal problems or failures in internal processes and require quick recovery. Therefore, complaint management must be well-designed. However, this will not be meaningful if failure, a cause of complaint, is not managed well. This article aims to establish a framework for failure management that can enhance the effectiveness of complaint management. Failure is a probability that can be prevented, anticipated, and managed. Failure management frameworks must be designed in accordance with global standards to achieve acceptance. In addition, the failure management framework must be flexible, robust, and comprehensive. Based on the definition of failure, ISO 31000:2018 provides a suitable basis for developing a failure management framework to enhance complaint management. Industry can utilize the findings to improve complaint management effectiveness by increasing stakeholder involvement in anticipating failures. This involves managing, assessing, preventing, handling, monitoring, reviewing, and recording failures to facilitate continuous improvement.